Cerebral Vasculitis in Ulcerative Colitis Is Predominantly Venular: Case Report and Review of the Literature - Paul T. Parks; Alexander S. Easton (Case Reports in Rheumatology)
Extraintestinal complications of ulcerative colitis include isolated case reports of cerebral vasculitis. In this case report, we describe autopsy findings in a 50-year-old female who died as a result of massive multifocal cerebral hemorrhage. Microscopic examination of the left colon showed findings typical for ulcerative colitis. Examination of the brain showed an extensive vasculitis. More affected vessels were noted in grey matter than in white matter. Many showed fibrinoid necrosis, invasion by neutrophils and thrombosis. There was extensive perivascular hemorrhage with associated infarction. Vessel analysis shows most of the vessels to have been venous rather than arterial. There were no perivascular sleeves of demyelination to suggest a primary demyelinating disorder, such as acute hemorrhagic leucoencephalitis. Our analysis shows that veins are the likely target of cerebral vasculitis in ulcerative colitis. This has clinical implications because venous occlusion generally causes massive intracerebral hemorrhage with a high mortality.